Melchizedek's alternative priestly order : a compositional analysis of Genesis 14:18-20 and its echoes throughout the Tanak - Mathews, Joshua G. (Bulletin for biblical research supplements, 2013)
Gen 14:18-20 is a brief episode depicting the encounter between Abram and Melchizedek. Taking this episode and its context in the Pentateuch as the starting point, Mathews sets out to analyze the text as it has been composed, in order to understand the biblical and theological significance of this priest-king Melchizedek. The thesis proposed and investigated is that Melchizedek's royal priestly portrayal in Genesis initiates a priesthood that is intentionally presented as an alternative to Aaron and his priesthood. The claim is that this distinct priestly order is evident in the biblical text as we have it, and it may be discerned by reading the text carefully, on its own terms, with close attention to its compositional features. --